New Parasite Records for the Sunfish Mola mola in the Mediterranean Sea and Their Potential Use as Biological Tags for Long-Distance Host Migration - Santoro, Mario; Palomba, Marialetizia; Mattiucci, Simonetta; Osca, David; Crocetta, Fabio (Frontiers in Veterinary Science, 2020)
Studies describing the parasite fauna of sunfish species from the Mediterranean Sea are to date limited, despite information gained through parasitological examination may reveal unknown ecological and biological aspects of both hosts and parasites. Moreover, recent molecular studies on sunfish taxonomy revealed the presence of two species belonging to the genus Mola in the Mediterranean basin, namely M. mola and M. alexandrini. These two fish taxa have long been synonymized or confused among them, which implies that the majority of the studies carried out so far reported the parasites infecting both species under a single host species, generally referred to as M. mola. We hereby investigated the parasite fauna of a 43 cm long M. mola specimen from the Mediterranean Sea, whose identification was confirmed by molecular tool, and provided the first evidence of the occurrence of the nematode Anisakis simplex (s.s.) and of the cestode Gymnorhynchus isuri in Mola species anywhere. The use of helminth species as biological tags for the sunfish is also discussed.